2022
DOI: 10.1055/s-0042-1745817
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculum Sella Meningioma: Surgical Management and Results with Emphasis on Visual Outcome

Abstract: Background Tuberculum sella meningioma form a distinct surgical entity with significant morbidity for the patient due to early and profound visual involvement. Surgical treatment of tuberculum sella meningioma is challenging in view of the proximity of vital neuro-vasculature. These lesions may be approached via a high-route (trans-cranial) or a low-route (trans-sphenoidal). Materials and Methods The authors present a consecutive series of 36 patients, operated by the first author from 1996 onward, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The mean size for the removal of the tuberculum sellae meningiomas has been reported to be 20-40 mm. 1 , 13 , 14 ) Tumor size in our patients was 10 and 25 mm, respectively. The size in the first patient was relatively small, and visual field deficits were relatively limited.…”
Section: Discussionmentioning
confidence: 53%
“…The mean size for the removal of the tuberculum sellae meningiomas has been reported to be 20-40 mm. 1 , 13 , 14 ) Tumor size in our patients was 10 and 25 mm, respectively. The size in the first patient was relatively small, and visual field deficits were relatively limited.…”
Section: Discussionmentioning
confidence: 53%
“…The main clinical manifestation of suprasellar meningiomas is visual impairment, 5,12 more prevalent in tumors originat-ing from TS, which makes the surgical resection of these lesions more beneficial. 2,13 According to our research, patients with TS-originating meningiomas exhibited a higher incidence of preoperative visual disturbances. Our analysis also revealed greater VA/VF deficits in OLF meningiomas, which may be attributable to the enormous tumor size of the included patients.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, we found no significant relationship between higher scores for optic canal invasion and decreased visual acuity or vascular invasion (Table 3). Several studies have described various factors affecting visual outcomes, such as young age and short symptom duration, which are good prognostic factors for visual outcomes [2,[16][17][18]. In addition, preoperative visual function, anterior cerebral artery encasement, and tumor size must be considered as influencing factors.…”
Section: Discussionmentioning
confidence: 99%